Reclaiming motherhood through shame, distance, and gratitude—A phenomenological study of Swedish women’s lived experiences of giving birth while ill with COVID-19 - Maria Revelj; Anna Wessberg; Ylva Carlsson; Maria Lindqvist; Verena Sengpiel; Karolina Linden (PLoS ONE, 2025)
Introduction Pregnant women were one of the most exposed and vulnerable groups during the COVID-19 pandemic. While much is known about the general effects of the pandemic on pregnant women’s well-being, little research has focused on the experiences of women who gave birth while infected with SARS-CoV-2. The aim of this study was to gain a deeper understanding of the lived experiences of women who gave birth while being ill with COVID-19. Materials and methods This is a qualitative study utilising a phenomenological reflective lifeworld approach to explore the lived experiences of Swedish women (n = 10) who gave birth while ill with COVID-19 between April 2020 and May 2021. Results The essence of the women’s experiences was described as ‘Reclaiming motherhood through shame, distance, and gratitude,’ supported by four constituents: “feeling intense shame and guilt for getting infected”,” striving to overcome distance in the birth setting”, “experiencing gratitude for receiving compassionate care” and “trying to comprehend motherhood and fighting to be reunited”. Conclusion A nuanced understanding of the experience at the intersection between childbirth, illness and the societal context is imperative for healthcare professionals and society to provide optimal care for one of the most vulnerable groups during pandemics, pregnant women and their newborns.